Peranan Orang Tua terhadap Motivasi Anak tentang Pengalaman Agama - Usman Sutisna (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2019)
This study aims to determine the significant role of parents on children's motivation in carrying out religious experience both at home and at school. The data collection method uses several techniques, namely; observation techniques, documentation, interviews with parents and stakeholders including principals and teachers, then questionnaires given to students in grades IV, V and VI amounting to 214 students, although the reverse questionnaire was 205 for further analysis. From the results of observations, interviews and statistical calculations of product moment correlation, it was obtained information that the religious experience of the students was strongly influenced by the role of parents and school management in order to habituate the religious behavior of students both at home and school. From the questionnaire processing, an average of more than 93,2% of students have been accustomed to performing five daily prayers and 90% fasting for ramadhan, even though the implementation of both services is based on their awareness or due to external factors namely the role of teacher and parental supervision